Design and synthesis of boron containing monosaccharides by the hydroboration of d-glucal for use in boron neutron capture therapy (BNCT). Issue 22 (1st December 2018) - Itoh, Taiki; Tamura, Kei; Ueda, Hiroki; Tanaka, Tomohiro; Sato, Kyouhei; Kuroda, Reiko; Aoki, Shin
Graphical abstract: Abstract: Boron neutron capture therapy (BNCT) is one of the radiotherapies that involves the use of boron-containing compounds for the treatment of cancer. Boron-10 ( 10 B) containing compounds that can accumulate in tumor tissue are expected to be suitable agents for BNCT. We report herein on the design and synthesis of some new BNCT agents based on ad -glucose scaffold, since glycoconjugation has been recognized as a useful strategy for the specific targeting of tumors. To introduce a boryl group into ad -glucose scaffold, we focused on the hydroboration ofd -glucal derivatives, which have a double bond between the C1 and C2 positions. It was hypothesized that a C–B bond could be introduced at the C2 position ofd -glucose by the hydroboration ofd -glucal derivatives and that the products could be stabilized by conversion to the corresponding boronic acid ester. To test this hypothesis, we prepared some 2-boryl-1, 2-dideoxy-d -glucose derivatives as boron carriers and evaluated their cytotoxicity and cellular uptake activity to cancer cells, especially under hypoxic conditions.